Onboarding software developers and teams in three globally distributed legacy projects: A multi‐case study. Issue 4 (3rd November 2017) - Britto, Ricardo; Cruzes, Daniela S.; Smite, Darja; Sablis, Aivars
Abstract: Onboarding is the process of supporting new employees regarding their social and performance adjustment to their new job. Software companies have faced challenges with recruitment and onboarding of new team members, and there is no study that investigates it in a holistic way. In this paper, we conducted a multi‐case study to investigate the onboarding of software developers/teams, associated challenges, and areas for further improvement in 3 globally distributed legacy projects. We employed Bauer's model for onboarding to identify the current state of the onboarding strategies employed in each case. We learned that the employed strategies are semi‐formalized. Besides, in projects with multiple sites, some functions are executed locally, and the onboarding outcomes may be hard to control. We also learned that onboarding in legacy projects is especially challenging and that decisions to distribute such projects across multiple locations shall be approached carefully. In our cases, the challenges to learn legacy code were further amplified by the project scale and the distance to the original sources of knowledge. Finally, we identified practices that can be used by companies to increase the chances of being successful when onboarding software developers and teams in globally distributed legacy projects.